Identity-based provable data possession scheme for multi-source IoT terminal data in public cloud - Huaqun WANG; Zhe LIU; Debiao HE; Jiguo LI (Tongxin xuebao)
To solve the problem of multi-source IoT data integrity verification, identity-based provable data possession for multi-source IoT terminal in public cloud (ID-MPDP) was proposed.Firstly, the formal definitions of system model and security model of ID-MPDP were given.Then, the specific ID-MPDP scheme was designed by using RSA.Finally, the performance analysis and security analysis of ID-MPDP were given.Through performance analysis and security analysis, ID-MPDP was provably secure, efficient and convertible.It has the following advantages, such as it can be used for the integrity checking for multi-source IoT terminal data, it has lower block expansion rate, it eliminates the certification management cost by using the identity-based public key cryptography and it is convertible.